1975
DOI: 10.1111/j.1365-2265.1975.tb01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triiodothyronine 7–15 Years After Fractionated Low Dose Radioiodine Therapy of Thyrotoxicosis

Abstract: In 189 of 334 patients, who had been treated with fractionated doses of radioiodine for Graves' disease 7-15 years ago, the serum concentrations of triiodothyronine have been estimated in additition to the following parameters: Protein bound 127-iodine (PB-127-I), free thyroxine index, cholesterol- and TSH-level in serum, tendon reflex time and clinical index according to Billewitz et al. (1969). In forty-one of the 189 sera the free T4 (AFT4) and free T3 (AFT3) concentrations were measured as well. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Incidence of hypothyroidism and patients with high TSH level In contradiction to the above postulations, some researchers insisted that T4 in the cited instances, though normal in level, was apparently insufficient for each individual to keep the metabolism ever normal, and TSH, sensitive to a very delicate change in T4 (Tunbridge et al 1974), accordingly increased in levels; and hence they recommended to place these cases in the category of subclinical hypothyroidism (Herrmann et al 1975). In another study, Toft et al (1975) made 3-year observe tion of their patients divided in the following two groups; one with T4 and TSH both normal, and the other with normal T4 and high TSH.…”
Section: Follow-up Studymentioning
confidence: 99%
“…Incidence of hypothyroidism and patients with high TSH level In contradiction to the above postulations, some researchers insisted that T4 in the cited instances, though normal in level, was apparently insufficient for each individual to keep the metabolism ever normal, and TSH, sensitive to a very delicate change in T4 (Tunbridge et al 1974), accordingly increased in levels; and hence they recommended to place these cases in the category of subclinical hypothyroidism (Herrmann et al 1975). In another study, Toft et al (1975) made 3-year observe tion of their patients divided in the following two groups; one with T4 and TSH both normal, and the other with normal T4 and high TSH.…”
Section: Follow-up Studymentioning
confidence: 99%
“…Furthermore, various authors have reported raised TSH values in a number ofconditions leading to thyroid insufficiency before any perceptible drop in the level of thyroid hormones or any clinical signs have been noted (Job et al, 1972;Hayek et al, 1973;Gordin et al, 1974). In this respect, raised TSH is one ofthe important biochemical indications of a state of premyxoedema (Ikram et al, 1973) or compensated hypothyroidism (Hayek et al, 1973;Barnes, 1975) which may develop into definite hypothyroidism, therefore justifying treatment with thyroid extracts (Hayek et al, 1973;Ikram et al, 1973;Evered et al, 1973;Young et al, 1975;Barnes, 1975;Rallison et al, 1975;Herrmann et al, 1975). The rise in TSH is an indicator whose sensitivity and specificity are useful for systematic screening.…”
Section: Discussionmentioning
confidence: 99%